(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The essay analyzes genre syncretism of Danica Marković’s poetry and recognizes several intimistic forms in her poems. In addition, it questions the usual definition of her poems as confessional and autobiographical verses and draws attention to the importance of diary patterns in her poetry. Bearing in mind her liberated female subjectivity, as well as her rebellious attitude toward the social prejudices of patriarchal culture, the text interprets the intimism of her verses from the gender studies perspective.